On some extensions of the Gołąb-Schinzel functional equation - Kahlig, Peter; Matkowski, Janusz (Annales Mathematicae Silesianae, 1994)
Composite functional equations (arising in applications) are presented that may be interpreted as extensions of the Gołąb-Schinzel equation and as modifications of d'Alembert's equation. Depending on the type of the considered equation, continuous, and finite rate of growth solutions are discussed. Geometric interpretations are given.